1880 Miss. Laws 21 - (:unkn) unknown (My University, 1880)
Ch. 6, § 7: Mandated tax assessors to have prepared rolls of taxable items, including pistols, Bowie knives, dirks, and sword canes.
Keywords: TAX - PROPERTY OR SALES